Adolescent Social Capital – An Intergenerational Resource? - Tuominen Minna; Tikkanen Jenni (Turn yliopisto, 2022)
Introduction: Social capital is a valuable asset that spawns multiple benefits, but little
is known about its origins. This study narrows the gap by exploring the extent to which
adolescents’ social capital is shaped by their parents’ social capital, the socioeconomic
status (SES) of their families, or that of their neighbourhood. The study also explores
which dimensions of adolescent social capital are most sensitive to intergenerational or
socioeconomic influence.
Methods: The study uses cross-sectional survey data gathered from adolescents aged
12–13 years and their parents (n = 167) in Southwest Finland. For the analysis,
adolescents’ social capital was disaggregated into four dimensions: social networks,
social trust, tendency to receive help, and tendency to provide help. For each dimension,
the associations with the hypothesised predictors were analysed separately using
structural equation modelling.
Results: The results suggest that parents’ social capital is the most influential predictor
to each dimension of adolescents’ social capital establishing stronger associations as
compared to the other two predictors. However, it is not the parents’ actual social
capital as they report themselves, but their offspring’s perception of their social
behaviour. Family’s SES relates to young people’s reciprocal tendency and level of trust
but only indirectly through parents’ social capital. Conversely, a disadvantaged
socioeconomic neighbourhood is directly negatively associated with adolescents’ level
of trust and frequency of receiving help.
Conclusions: This study suggests that social capital is distinctly, although not
exclusively, an intergenerational resource. Parents are critical role models for adolescent
children